Electrospun Bilayer Membrane: Metal–Electrolyte Solution Dual‐Mode Electrospinning Process for In Situ Fabrication of Electrospun Bilayer Membrane (Adv. Mater. Interfaces 20/2020). Issue 20 (23rd October 2020) - Han, Hyeonseok; Hong, Hyeonjun; Park, Sang Min; Kim, Dong Sung
Abstract : Metal–electrolyte solution dual‐mode electrospinning (M‐ELES) is developed for in situ fabrication of electrospun bilayer membrane of aligned and random nanofiber layers with a novel switchable collector. The bilayer membrane promotes wound coverage of cells by aligned nanofibers while providing mechanical support by random nanofibers. More details can be found in article number 2000571 by Dong Sung Kim and co‐workers.